2016
DOI: 10.1108/lodj-12-2014-0242
|View full text |Cite
|
Sign up to set email alerts
|

Why does leader attention scope matter for innovation ambidexterity? The mediating role of transformational leadership

Abstract: Purpose The purpose of this paper is to explore the role leader attention plays in the nurture of transformational leadership (TL) behavior, as well as the mechanism by which TL affects innovation ambidexterity, this research empirically studied the relationship between leader attention scope (LAS) and innovation ambidexterity (exploratory innovation and exploitative innovation) through the mediating role of TL. Further, the moderating effect of environmental dynamism (ED) on the relationship between TL and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 98 publications
(151 reference statements)
3
38
0
2
Order By: Relevance
“…Chen & Fiore (2017) proposed the close relationship between organizational management innovation and corporate technology innovation. Zheng et al (2016) found out positive eff ects of the combination of technology innovation (product and process) and non-technology innovation (organization and marketing) on organizational profi t-making. Garaus et al (2016) included product innovation and process innovation in corporate technology innovation; product innovation could have enterprises keep diff erential advantage from competitors, while process innovation allowed enterprises achieving cost advantage.…”
Section: Research Hypothesismentioning
confidence: 95%
“…Chen & Fiore (2017) proposed the close relationship between organizational management innovation and corporate technology innovation. Zheng et al (2016) found out positive eff ects of the combination of technology innovation (product and process) and non-technology innovation (organization and marketing) on organizational profi t-making. Garaus et al (2016) included product innovation and process innovation in corporate technology innovation; product innovation could have enterprises keep diff erential advantage from competitors, while process innovation allowed enterprises achieving cost advantage.…”
Section: Research Hypothesismentioning
confidence: 95%
“…Samad (2012) stated that TL is considered important to organizations as they integrate creative insight, persistence and are sensitive to their employees that prompt changes in management innovation regarding practices and processes. Zheng et al (2016) argued that transformational leader by sharing goals, values and beliefs among team members encourages them to work together effectively and develop innovative ways to succeed. Through the TL, leaders can contribute to the employees' creativity by recognizing individual differences and encouraging more diverse approaches and perspectives (Guo et al, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Several leadership styles have been studied, however, the best-known leadership style and the most widely used in leadership literature that linked to innovation is TL (Alnesr and Ramzani, 2019;Michaelis et al, 2010;Zheng et al, 2016). This style plays an essential role in developing the process, structure and climate for firms to become innovative (Chan et al, 2014;Yukl, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations